A Comparison of Distance and On-Campus Learning Models to Prepare Teachers of Students With Visual Impairments. (May 2022) - Hong, Sunggye; Topor, Irene; Erin, Jane
Introduction: Since the 1970s, many universities and agencies have prepared professionals in visual impairment through distance educational approaches, including concentrated off-campus courses, video and telephone connections, and synchronous or asynchronous online methods. Although online professional preparation in visual impairment has become common, there is little data that compares outcomes of on-campus instruction with distance education methods. This article reports follow-up data from a federally funded graduate university program that prepares teachers of students with visual impairments: It compares results from a survey that describes how on-campus and distance education students perceived the quality of their preparation. Methods: An online survey was sent to 37 bachelor's degree students who had earned certification as teachers of students with visual impairments. 27 students returned usable surveys, in which they reported relevant demographic information and current job roles. The survey included 13 demographic questions about employment and setting. Eight questions related to general evaluation of their preparation program, and 22 questions related to perceived competence in skills needed to prepare teachers of students with visual impairments. Results: There were few differences between perceptions of students who were prepared in the full-time on-campus model and those who were prepared through distance education. Most respondents were graduates working as itinerant teachers in public schools or specialized school settings. With regard to perceptions of their own skills related to visual impairment, only the item on assistive technology showed a significant difference between the two models. Students in distance education perceived themselves as less well prepared in that area. Discussion: Given the increased shift toward distance learning caused by the COVID-19 virus, the authors suggest that a broad-based national study of outcomes related to distance learning in visual impairment might offer more detailed insights into the quality of teaching produced through distance learning.